Lodare la lode. Il trattatello di Speroni sul genere dimostrativo - Teodoro Katinis (Fabrica Litterarum Polono-Italica)
This contribution presents an analysis of the short treatise De genere demonstrativo by the Paduan rhetorician and philosopher Sperone Speroni (1500–1588), a highly relevant figure of the Italian Cinquecento. The main point of Speroni’s treatise is to defend demonstrative rhetoric against its detractors and to give it a larger space than Aristotle did in his Art of Rhetoric. I focus on the dialogue of the text with the rhetorical tradition and on the original aspects of Speroni’s argumentation in favor of praise, with particular attention to the technique of amplification. In conducting this examination, I highlight some of the rhetorical strategies that Speroni himself applies in praising praise.